From Iron to Glass: Transparency and Pluralism - Maryse Fauvel (Studies in 20th & 21st Century Literature, 1996)
The author reads a number of recent architectural constructions in Paris (mainly the Louvre pyramid, but also the Musée d'Orsay and the Institut du monde arabe) and argues that they affirm the plurality of contemporary France while at once inscribing and subverting the conventions of its (once) dominant culture: the Arab world in the heart of Paris, the museum cum railway station as the focal point of conflicting tastes, the pyramid as both accomplice and critic of history. Their pluralism qualifies them as postmodern. These monuments also propose a new role for today's museum. The building itself becomes an art object, and the museum is not reduced to its function as a place for education and edification; it demands an inventive and exploratory initiative on the part of the visitor.
Keywords: architectural constructions; Paris; Louvre pyramid; architecture; Musée d' Orsay; Institut du monde arabe; plurality; contemporary France; inscribing; subverting; dominant culture; Arab; Arab world; museum; railway station; conflict; taste; pluralism; postmodern; history; criticism; art object; building; art; education; edification; visitor